As Faces da Perturbação Afetiva Bipolar: Abordagem Multifatorial nos Cuidados de Saúde Primários - Liliana Ferreira Rodrigues Silva (2021)
Introduction: Despite affecting only about 2% of patients in primary care, bipolar disorder is one of the most disabling disorders worldwide. Therefore, its accurate diagnosis constitutes an element of high relevance in its clinical approach. Materials and Methods: We performed a literature review regarding diagnostic aspects of bipolar disorder, particularly in the primary care setting and the connection with other health services. In this context, we conducted a bibliographic search in Web of Science database and reviewed articles published between 2016 and 2020. Results: Bipolar disorder is mostly underdiagnosed, and its common comorbidities are underestimated. Hence, these patients usually die earlier than the general population. Considering the complexity inherent to this pathology, the intervention of primary care professionals is extremely important alongside the provision of collaborative care. Discussion/Conclusion: Despite the progression of scientific knowledge, it is not possible to prevent bipolar disorder currently. Given this, the best medical approach is based primarily on early recognition of this mental illness. Therefore, primary care physicians must be aware of its details.